1983
DOI: 10.2135/cropsci1983.0011183x002300030018x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Soybean Lines Selected for Divergent Leaf Photosynthetic Ability1

Abstract: One way to enhance net photosynthate production in soybean [Glycine max (L.) Merr.] may be to breed genotypes with accelerated leaf photosynthetic rates. The objective of this experiment was to determine the effects of divergent selection for 14CO2‐uptake rate per unit leaf area, total photosynthesis (TPs), on seed yield and canopy growth. Eighteen F7‐derived lines were grown in the field. These included nine lines previously selected for rapid TPs and nine selected for slow TPs. Total photosynthesis was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…No doubt, grain yield is the end product of several factors and there is no direct relationship between photosynthesis and yield. Selection for higher photosynthesis in maize (GROSBIE and PEARCE 1982) and in soybean (FoRDE et al 1983) did not result in higher grain yields. However, altered environments to enhance photosynthesis, increased the biomass or grain yield of wheat (FISCHER andAGUILAR 1976, THORNE andWOOD 1987).…”
Section: Discussionmentioning
confidence: 93%
“…No doubt, grain yield is the end product of several factors and there is no direct relationship between photosynthesis and yield. Selection for higher photosynthesis in maize (GROSBIE and PEARCE 1982) and in soybean (FoRDE et al 1983) did not result in higher grain yields. However, altered environments to enhance photosynthesis, increased the biomass or grain yield of wheat (FISCHER andAGUILAR 1976, THORNE andWOOD 1987).…”
Section: Discussionmentioning
confidence: 93%
“…In the United States, research has shown cultivar differences for photosynthetic rate in soybean (Dornhoff and Shibles, 1970) and a positive correlation between CAP and yield (Wells et al, 1982). Wiebold et al (1981) concluded that early‐generation selection for CO 2 exchange rate in soybean was ineffective, but Ford et al (1983) found differences in photosynthetic rates in 20 lines after seven generations of selection for the trait (although there was no significant effect on yield or harvest index). Ashley and Boerma (1989) found a positive correlation between CAP during seed fill and yield from F 3 –derived lines from two crosses.…”
Section: Discussionmentioning
confidence: 99%
“…Wiebold et al (1981) crossed two parental cultivars with contrasting high and low CER and could not find improved CER by the F 3 and F 4 generations. Ford et al (1983) found similar disappointing results. The current general consensus is that using CER as an indirect selection criterion in a breeding program has limited value (Frederick and Hesketh, 1994).…”
Section: Genetic Strategies For Yield Improvementmentioning
confidence: 72%